Pengolahan ikan bandeng dengan menggunakan alat mesin pemisah tulang di Kecamatan Maros Baru Kabupaten Maros - Jamaluddin Jamaluddin; Amirah Mustarin; Khaidir Rahman (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
PKM milkfish processing with the use of bone separating machine tools in Maros Baru District Maros Regency is anew technology and innovation that will be implemented to answer the problem of difficulties in processing milkfish that hasmany thorns. Milkfish is one of the many ponds produced in Maros Regency but this type of fish is rarely processed into nuggetsprocessed products because of difficult spines. The fishery products produced namely fish increase the selling value of milkfishthrough training on fish processing technology based on meat and thorn separator machines, opening job opportunities, andproviding new experiences for partners in making processed fish products for the Sikamaseang Group. This PKM is carried outin 2 stages, namely the training and assistance phase. The training was conducted using lecture methods, participatorydemonstrations, and practices that involved all program participants. Group assistance is carried out in coordination with the localagricultural instructor in the development of the partner group's milkfish processing unit. The results of these activities are milkfish nuggets and skills to use a fish bone separator tool. Knowledge and skills about bone and fish separator tools and the makingof nuggets can motivate program participants to develop a processing business unit in Maros Baru District, Maros Regency.